Lamin B1 protein is required for dendrite development in primary mouse cortical neurons - Giacomini, Caterina; Mahajani, Sameehan; Ruffilli, Roberta; Marotta, Roberto; Gasparini, Laura (Molecular biology of the cell, 2016)
Lamin B1, a key component of the nuclear lamina, plays an important role in brain development and function. A duplication of the human lamin B1 ( LMNB1) gene has been linked to adult-onset autosomal dominant leukodystrophy, and mouse and human loss-of-function mutations in lamin B1 are susceptibility factors for neural tube defects. In the mouse, experimental ablation of endogenous lamin B1 (Lmnb1) severely impairs embryonic corticogenesis. Here we report that in primary mouse cortical neurons, LMNB1 overexpression reduces axonal outgrowth, whereas deficiency of endogenous Lmnb1 results in aberrant dendritic development. In the absence of Lmnb1, both the length and complexity of dendrites are reduced, and their growth is unresponsive to KCl stimulation. This defective dendritic outgrowth stems from impaired ERK signaling. In Lmnb1-null neurons, ERK is correctly phosphorylated, but phospho-ERK fails to translocate to the nucleus, possibly due to delocalization of nuclear pore complexes (NPCs) at the nuclear envelope. Taken together, these data highlight a previously unrecognized role of lamin B1 in dendrite development of mouse cortical neurons through regulation of nuclear shuttling of specific signaling molecules and NPC distribution.